Biochar-Modified BiOBr Photocatalyst for Enhanced Visible-Light-Driven Degradation of Antibiotics - Yue Zhang; Yanlin Wu; Defa Hou; Xijuan Chai (International Journal of Environmental Research, 2026)

A novel dual-parameter method for evaluating seismic collapse severity in masonry pagodas - Mingdong Li; Junlong Lu; Defa Wang; Xin Jia; Xiaoqin Wu; Dongxu Mao; Zuoyi Yun; Zhenshan Wang (Bulletin of Earthquake Engineering, 2026)

Water Injection Failure of Full-Ocean-Depth Adjustable Ballast System: Mechanism Analysis and Experimental Verification - Zhida Chen; Sheng Zhou; Jize Jiang; Linglong Li; Cong Ye; Shuai Liu; Defa Wu; Yunxiang Ma; Lang Gu (Journal of Marine Science and Engineering, 2026)
Reliable operation of adjustable ballast systems is essential for full-ocean-depth manned submersibles, but existing studies mostly focus on component-level performance optimization, leaving the multi-valve coupled instability mechanism under ultra-high pressure insufficiently understood. This paper investigates an uncontrolled water injection failure in the adjustable ballast system of the “Fendouzhe” submersible via fault tree analysis, high-pressure physical tests and AMESim dynamic simulations. Results show that the initial fit clearance of the downstream flow valve is the dominant prerequisite for instability, and a fluid–structure interaction positive feedback loop between the series valve assembly drives the flow surge fault. Removing the series flow valve fundamentally interrupts the coupling feedback loop. Full-range 0–115 MPa bench tests and follow-up sea trials confirm that the modified system eliminates the observed flow surge within the tested pressure range and operating conditions. This work provides a practical diagnostic framework and engineering reference for reliability design of high-pressure seawater hydraulic systems.

Corrigendum to “Analysis and optimization of opening characteristics of deep-sea water hydraulic safety valve” [Ocean Eng. 344, 15 (January 2026), 123682] - Jize Jiang; Jiefu Liu; Jiangxiong Li; Boyang Zhang; Xiguang Hu; Yinshui Liu; Defa Wu (Ocean Engineering, 2026)

Analysis and optimization of opening characteristics of deep-sea water hydraulic safety valve - Jize Jiang; Jiefu Liu; Jiangxiong Li; Boyang Zhang; Xiguang Hu; Yinshui Liu; Defa Wu (Ocean Engineering, 2026)

Theoretical and experimental study on the performance of the hydraulic power unit employed on full ocean depth manned submersible - Zhida Chen; Tianhao Li; Linglong Li; Jincang Liao; Cong Ye; Defa Wu; Shuai Liu; Yinshui Liu; Yunxiang Ma; Lang Gu; Gang Sun (Ocean Engineering, 2025)

Research on vector layout of ducted propellers for remotely operated vehicle - Cong Xue; Yu Dai; Jize Jiang; Guanghao Ren; Defa Wu (Ocean Engineering, 2025)

An investigation of scouring mechanism and equilibrium state by the submerged jet using synthesized oblique velocity - Xiguang Hu; Zhida Chen; Xing Yang; Linglong Li; Defa Wu; Yunxiang Ma; Yinshui Liu (Ocean Engineering, 2025)

Development of a Six-Degree-of-Freedom Deep-Sea Water-Hydraulic Manipulator - Heng Gao; Defa Wu; Chuanqi Gao; Changkun Xu; Xing Yang; Yinshui Liu (Journal of Marine Science and Engineering, 2024)
With the advancement of deep-sea exploration, the demand for underwater manipulators capable of long-duration heavy-duty operations has intensified. Water-hydraulic systems exhibit less viscosity variation with increasing depth than oil-based systems, offering better adaptability to deep-sea conditions. Using seawater as the driving medium inherently eliminates issues such as oil contamination by water, frequent maintenance limiting underwater operation time, and environmental pollution caused by oil leaks. This paper introduces a deep-sea manipulator directly driven by seawater from the deep-sea environment. To address the challenges of weak lubrication and high corrosion associated with water hydraulics, a reciprocating plunger seal was adopted, and a water-hydraulic actuator was developed. The installation positions of actuator hinges and maximum output force requirements were optimized using particle swarm optimization (PSO), effectively reducing the manipulator’s self-weight. Through kinematic and inverse kinematic analyses and joint performance tests, a six-degree-of-freedom water-hydraulic manipulator was designed with a maximum reach of 2.5 m, a lifting capacity of 5000 N, and end-effector positioning accuracy within 18 mm.